The Numerical Reliability of Econometric Software - McCullough, B. D; Vinod, H. D (Journal of Economic Literature, 1999)
Numerous examples show that some econometric software packages contain serious flaws, and that users cannot safely assume that their software is accurate. A brief survey of the fundamentals of computer arithmetic discusses the sources of numerical error and emphasizes that computer arithmetic is not at all like pencil-and-paper arithmetic. Both users and developers of econometrics software should first pay attention to accuracy, and only later consider user-friendliness. Details are provided for assessing the accuracy of basic estimation routines, statistical distributions, and random number generators. More accuracy benchmarks are needed, especially for specialized econometric procedures.